Reconfigurable shape-morphing dielectric elastomers using spatially varying electric fields - Ehsan Hajiesmaili (Nature Portfolio, 2019)
Electric fields can produce strains in soft elastomers but a generalizable method for changing the Gaussian curvature has not been devised. Here the authors demonstrate voltage-tunable shape morphing using a spatially inhomogeneous electric field generated by electrodes incorporated between elastomer layers.